Sustainable Tourism and Natural Resource Conservation in the Polar Regions - Machiel Lamers (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This book holds key papers from the fifth conference and community workshop of the International Polar Tourism Research Network (IPTRN), held in the village of Raufarhöfn (population 160) in Northeast Iceland at the end of August 2016. In total, 40 papers were presented at the conference which explored how expectations towards tourism development in peripheral places can be managed to contribute to the cultural well-being of peripheral communities and enhance the protection of the environment. The seven papers contained herein, in addition to the editorial, can roughly be grouped into two categories. The first set of four papers deals with methods and key assets for developing sustainable tourism operations in the Polar Regions. The second set of three papers deals more with the implications of different means of access to the more remote parts of the Polar Regions.